(untitled) (ESMAT Magazine, 2024)
The crime of smuggling is included in the scope of cross-border crime, which is characterized by involving more than one country in its execution. This crime considers the internalization in Brazil or externalization in another country of products that are relatively or absolutely prohibited. Pesticides become a material object of this conduct if there is no authorization for their use in the country due to the active ingredient used or the percentage incorporated in the product. It can be seen, however, that the western region of Paraná, where the border with Paraguay is located, is also one of the largest agricultural areas producing grains. Prohibited pesticides represent greater effectiveness against pests as they are more toxic, in addition to reducing the use of inputs and labor. Therefore, they represent greater profitability for agribusiness. On the other hand, they bring significant harm to the environment and the health of those who are directly or indirectly exposed to their use. This crime therefore brings numerous challenges in its containment, not only due to the extension of the border or the lack of supervision, but because it is connected to other forms of crime and social and economic values that normalize such behavior.